2020
DOI: 10.1021/acsomega.0c03944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solvent Debinding on the Microstructure and Properties of 3D-Printed Alumina Ceramics

Abstract: Solvents assist in the debinding of stereolithography-based 3D-printed alumina green bodies. The green bodies subsequently undergo thermal debinding and sintering to obtain alumina ceramics. In this study, several solvents were tested, including polyethylene glycol, oxalic acid, ammonium hydroxide, ethyl alcohol, methyl methacrylate, butyl acetate, dimethyl carbonate, methanol, ethyl acetate, and sec -butyl alcohol. The tested solvents during the debinding process showed different effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The flexural strength was approximately 30% higher compared to results obtained by SLS–255 MPa (4PB), reported by Li et al [ 38 ], and 26% higher than conventionally manufactured alumina by powder injection molding with 264 MPa (3PB) reported by J. Y. Roh [ 31 ]. The results are 21% lower (427 MPa, 4PB) compared to the LCM technology reported by Schwentenwein and Homa Schwentenwein and Homa [ 25 ].…”
Section: Resultsmentioning
confidence: 59%
“…The flexural strength was approximately 30% higher compared to results obtained by SLS–255 MPa (4PB), reported by Li et al [ 38 ], and 26% higher than conventionally manufactured alumina by powder injection molding with 264 MPa (3PB) reported by J. Y. Roh [ 31 ]. The results are 21% lower (427 MPa, 4PB) compared to the LCM technology reported by Schwentenwein and Homa Schwentenwein and Homa [ 25 ].…”
Section: Resultsmentioning
confidence: 59%
“…This can be explained by the microstructure where porosities or particles are oriented parallel to the manufacturing axis 14,[24][25][26] . Some authors have shown that the shrinkage ratios calculated in the same plane of the printed layer are similar 14,[26][27][28] . However, another study has shown that the anisotropic shrinkage ratio (A)…”
Section: Introductionmentioning
confidence: 92%
“…The samples that used oxalic acid as a solvent have shown maximum flexural strength of 63.4 MPa. 137 The butanoneethanol azeotropic solvent is used for the fine dispersion of Al 2 O 3 /SiC whiskers and UV resins. The Al 2 O 3 /SiC part fabricated by the SLA process has shown a fracture toughness of 7.1 MPa•m 1/2 and a hardness of 17.6 GPa.…”
Section: Table 2 Mechanical Properties Of Human Bonementioning
confidence: 99%